Pelatihan Menulis Deskripsi Bagi Siswa Tuna Rungu - Kustini, Titin; Syarifah, Eva Fitriani (FKIP Universitas Majalengka, 2025)
Sustainable Development Goal 4 is about Quality Education, namely ensuring inclusive and equitable quality education and increasing lifelong learning opportunities for all. This is emphasized in target 4. A, namely building and improving child-friendly, disability-friendly, and gender-friendly educational facilities, and providing a safe, non-violent, inclusive, and effective learning environment for all. However, in reality, inclusive education in Indonesia still requires extra attention. This community service aims to provide training in writing descriptions to deaf students at SLB B YPLB Majalengka. This activity was attended by 5 students (5 boys and 2 girls) from the SMPLB and SMALB levels. Participants were trained to write self-descriptions that included their names, addresses, age, aspirations, and school experiences. The training was carried out through a participatory approach by providing examples, structured exercises, and direct assistance. The results of the activity showed that all participants were able to follow the training well and produce structured and contextually appropriate descriptive texts. This activity contributes to improving the writing and self-expression skills of deaf students. These findings suggest that with proper guidance and easily accessible materials, deaf students can be actively involved in learning descriptive writing.